2020
DOI: 10.1177/0300891620930803
|View full text |Cite
|
Sign up to set email alerts
|

Association of high TUBB3 with resistance to adjuvant docetaxel-based chemotherapy in gastric cancer: translational study of ITACA-S

Abstract: Background: No predictive markers for chemotherapy activity have been validated in gastric cancer (GC). The potential value of class III β-tubulin (TUBB3) as biomarker for prognosis and resistance to taxane-based therapy was reported. Methods: We analyzed GC samples of patients enrolled in the Intergroup Trial of Adjuvant Chemotherapy in Adenocarcinoma of the Stomach (ITACA-S), a randomized adjuvant study comparing 5-fluorouracil/leucovorin (5-FU/LV) and docetaxel-based sequential chemotherapy. TUBB3 was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…TUBB3 belongs to the family of tubulin proteins being part of microtubules and has been intensively studied as a possible predictor of the efficacy of antitumor agents from the taxane group [1][2][3][4][5]. The uniqueness of TUBB3 as a potential tumor-associated marker is that it is practically not detected in normal epithelial cells [6] and is expressed only at low intensity in endotheliocytes and macrophages [7].…”
mentioning
confidence: 99%
“…TUBB3 belongs to the family of tubulin proteins being part of microtubules and has been intensively studied as a possible predictor of the efficacy of antitumor agents from the taxane group [1][2][3][4][5]. The uniqueness of TUBB3 as a potential tumor-associated marker is that it is practically not detected in normal epithelial cells [6] and is expressed only at low intensity in endotheliocytes and macrophages [7].…”
mentioning
confidence: 99%
“… 29–32 Patients with high expression of TUBB3 exhibit poor survival rate and resistance to docetaxel, paclitaxel- and cisplatin-based chemotherapies. 24 , 33–37 Head and neck cancer patients positive for TUBB3 expression and undergoing induction chemotherapy with 5-Flurouracil (5-FU) and cisplatin and 5-FU, cisplatin and docetaxel exhibited lower response rate. In addition, they also showed a higher disease progression and reduction in overall survival rate compared to TUBB3-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…TUBB3 was also found both in GSE19860 and GSE3964. One research suggested that patients with high TUBB3 had a statistically significant poorer OS when undergoing docetaxelbased versus 5-FU/LV chemotherapeutic (21).…”
Section: Identification Of 5-fu Resistance and Immune Both Related Genesmentioning
confidence: 99%